2002
DOI: 10.1007/s00280-002-0516-5
|View full text |Cite
|
Sign up to set email alerts
|

Development of an optimal pharmacokinetic sampling schedule for rubitecan administered orally in a daily times five schedule

Abstract: An optimal sampling schedule was derived which allowed assessment of the pharmacokinetic parameters of both the parent compound and its metabolite 9-AC after oral administration of rubitecan.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 13 publications
1
10
0
Order By: Relevance
“…In our previous studies of 9NC, most of the drug remained in the 9NC form, with a mean 9NC to 9AC ratio of 4 to 1, which is consistent with other previous studies [6][7][8].…”
Section: Introductionsupporting
confidence: 89%
See 3 more Smart Citations
“…In our previous studies of 9NC, most of the drug remained in the 9NC form, with a mean 9NC to 9AC ratio of 4 to 1, which is consistent with other previous studies [6][7][8].…”
Section: Introductionsupporting
confidence: 89%
“…Several studies have evaluated the relationship between ABC genotypes and disposition of camptothecin analogues [5,22,23,[36][37][38][39][40]. 9NC is an orally administered camptothecin analogue with significant interpatient variability in drug disposition [6][7][8][9][10]. This is the first study that compares the disposition of 9NC and its 9AC metabolite to the ABCB1, ABCC2, and ABCG2 genotypes in patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Pharmacokinetics performed on days 1 and 15 suggested induction of 9-NC metabolism, since clearance was higher on day 15 relative to day 1 at each dose level (although significant only at 2.25 mg/day). The increase in 9-NC clearance was possibly due to reduction of the nitro group of 9-NC, yielding 9-AC [10][11][12]. Additional in vitro studies indicated that 9-NC metabolism to 9-AC may be mediated through Table 5 Grade One patient (breast cancer with peritoneal carcinomatosis) with grade 3 nausea, vomiting, and dehydration were aggravated by partial bowel obstruction c One patient (breast cancer) with grade 3 nausea and vomiting.…”
Section: Discussionmentioning
confidence: 97%